System and Method for Generating Amorphous Dynamic Display Icons (2022)
A system and method for generating amorphous randomized and/or fuzzy logic dynamic display icons that visually communicate to its users and/or entities that a subject's geographic location is being obfuscated on a graphical mapping interface of the user's computing device by way of continuously generating a dynamic location display icon having amorphous and/or asymmetrical shape, size, position, color, opacity, outline, movement, and/or transformation rate, and displaying the generated dynamic display icon on the graphical mapping interface.